PENINGKATAN MUTU SUMBER DAYA MANUSIA DI ERA DISRUPSI DAN MAHASISWA SEBAGAI AGEN PERUBAHAN 5.0: PENINGKATAN MUTU SUMBER DAYA MANUSIA DI ERA DISRUPSI DAN MAHASISWA SEBAGAI AGEN PERUBAHAN 5.0 - sumantri, irman (Universitas Negeri Jakarta, 2022)
Superior human resources are the greatest asset for a country, with superior quality human resources, a country will be able to easily keep up with the developments of this very fast era, not only that superior human resources are an illustration of the success of the existing management of educational institutions. in a country. This study uses a literature review method which includes searching for references such as journals, books and reading materials on the internet. In this era of disruption, the development of human resources is very crucial and vital. It is not only from the government that must strive to improve the quality of human resources, but the role of students is very decisive because they are educated people who have critical thinking power and deep disciplines in various fields